1991
DOI: 10.1007/bf02565125
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal size and bone mineral content in Turner's syndrome: Relation to karyotype, estrogen treatment, physical fitness, and bone turnover

Abstract: Bone mineral content (BMC), bone mineral density, and metacarpal dimensions were studied in 50 women with Turner's syndrome aged 21-45 years in relation to karyotype, estrogen treatment, physical fitness, and biochemical markers of bone turnover. No differences were found between the 25 women with karyotype 45.X and women with other karyotypes. Forty-six women had received estrogen. Significant partial correlations were found between bone mineral density of the forearm and duration of estrogen treatment and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 46 publications
4
41
1
1
Order By: Relevance
“…Treatment with estrogens is needed to induce maximal peak bone mass in adolescents and young adults (145,253,258,259). This is supported by four longitudinal studies of estrogen deficient as well as estrogen replete adolescents with TS.…”
Section: Hrt Gh and Bonementioning
confidence: 96%
See 2 more Smart Citations
“…Treatment with estrogens is needed to induce maximal peak bone mass in adolescents and young adults (145,253,258,259). This is supported by four longitudinal studies of estrogen deficient as well as estrogen replete adolescents with TS.…”
Section: Hrt Gh and Bonementioning
confidence: 96%
“…orally or from sunlight) of 25-OH-D or reduced uptake of the compound (76,249). It is uncertain whether the reduced BMD is solely attributable to estrogen deficiency (243,244,246,253). Recently, we observed that the increased risk of fractures in TS was present already in childhood and persisted throughout all age groups (8).…”
Section: Spontaneous Accretion Of Bone Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteopenia or even osteoporosis is a common factor in Turner syndrome patients [5, 6, 7, 8, 9, 10, 11, 12, 13]. Skeletal growth is a continuous process during infancy, childhood and adolescence which peaks in the early twenties [20, 21, 22, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian dysgenesis, short stature and osteopenia are among the main clinical features [1, 2, 3, 4]. Osteopenia or even osteoporosis have been reported in cross-sectional studies in adult patients on estrogen/gestagen therapy, and have been related either to an intrinsic bone defect or a lack of adequate estrogen/gestagen availability to bone tissue [5, 6, 7, 8, 9, 10, 11, 12, 13]. …”
Section: Introductionmentioning
confidence: 99%